In Vitro Effect of a High-Intensity Laser on Candida albicans Colony Count: In Vitro Effect of High-Intensity Laser - Momeni, Ehsan; Didehdar, Mojtaba; Sarlak, Elham; Safari, Malihe (Journal of Lasers in Medical Sciences, 2022)
Introduction: This study assessed the effect of high-intensity laser on Candida albicans (C.albicans) colony count. Methods: In vitro, an experimental study was conducted on standard-strain C. Albicans (ATCC18804). Seventy-two samples with two different concentrations of C. Albicans (104 cells/mL and 106 cells/mL) were randomly assigned to three groups of control, laser, and nystatin. Each group included 12 samples from each concentration. In the nystatin group, 10 cc of nystatin suspension was added to the samples and mixed for 30 60 seconds. In the laser group, the Ga-Al-Ar diode laser with 940 nm wavelength and 2 W power was irradiated to the samples with 0.4 mm tip diameter in non-contact mode (1 mm distance) at a speed of 1 mm/second. The suspensions in the three groups were cultured on Sabouraud dextrose agar culture medium and incubated at 37°C for 24 hours. The number of C. Albicans colonies was then counted and reported. The three groups were compared by ANOVA and Tukey’s test (alpha=0.05). Results: In both concentrations, the mean colony count in the nystatin group was significantly lower than that in the control (P<0.05) and laser (P<0.05) groups. The mean colony count in the laser group was significantly lower than that in the control group (P<0.05). Conclusion: High-intensity laser with 940 nm wavelength and 2 W power in non-contact mode can significantly decrease the C. Albicans colony count in vitro, but its effect is lower than that of nystatin.